Implementing AI in Preschool Education: Pedagogical, Ethical, and Cultural Dimensions in the Cyclades, Greece - Zoi Apostolou; Irini Psarra (Journal of Research in Education and Pedagogy, 2026)
The accelerating integration of Artificial Intelligence (AI) into contemporary education has generated both opportunities and challenges across all educational levels, including early childhood education. This study investigates the perceptions, attitudes, and practices of kindergarten teachers in the Cyclades regarding the incorporation of AI into their pedagogical work. It aims to identify the perceived benefits and limitations of AI applications in early learning environments, as well as the extent to which prior professional training influences teachers’ readiness to adopt such technologies. An anonymous structured online questionnaire (five-point Likert scale) was employed to collect data on teachers’ knowledge, attitudes, and classroom practices related to AI. The findings reveal that participants generally acknowledge the pedagogical potential of AI to support creativity, individualized learning, and instructional efficiency. Nonetheless, significant concerns persist regarding data privacy, algorithmic bias, and the possible erosion of the interpersonal dimension that characterizes early childhood education. Statistical analysis (SPSS v.29) further indicates that teachers who have participated in AI-related training programs exhibit more favorable attitudes and a higher level of self-efficacy in implementing innovative digital tools. Overall, the results suggest that kindergarten educators in the Cyclades possess a basic conceptual understanding of AI and already apply its elements in practice, albeit cautiously and selectively. The study underscores the need for systematic and ethically informed teacher training programs that emphasize the critical use of AI as a supportive—not substitutive—agent in early education. Such an approach aligns with a pedagogical vision where technological innovation remains firmly grounded in human values and educational purpose.